ENSURING AND GUARANTEEING THE PETITION RIGHT IN ROMANIA AND THE REPUBLIC OF MOLDOVA - Cătălin-Radu PAVEL (Challenges of the Knowledge Society, 2021)
The aim of the present study is to analyze the ensuring and guaranteeing the petition right in Romania and Republic of Moldova as a consequence for ensuring of a good administration. The objectives of this study were to analyze the petition right as a fundamental guarantee and the correlation with ensuring of a good administration. In this research we have highlighted the importance of granting the petition right for the citizens and the contribution to the developing of a good administration of the state in the favor of the citizens.